Study on Flotation of Low-rank Coal Slime with Binary Mixed Collector - Cheng GAN; Biyang TUO; Jianli WANG; Yun TANG; Guanghua NIE; Zhengbin DENG (Kuangchan zonghe liyong, 2025)
In order to improve the collection performance of diesel on low-rank slime flotation, the binary mixed collector prepared by compounding diesel and oleic acid was used as the collector for low-rank slime flotation in this study. The mechanism of the synergistic effect of diesel oil and oleic acid on improving the flotation of low-rank coal slime was explored by the contact angle test and Zeta potential test. The results show that when the mass ratio of diesel and oleic acid is 3∶2(3C2Y) and the amount of collector is 1 kg/t, the clean coal yield and combustible recovery rate are the highest, which are 65.66% and 88.91% respectively. After 3-stage flotation, the ash content of clean coal was reduced to 24.44%. The synergistic effect of diesel oil and oleic acid increases the contact angle of the coal particle surface by 25° and reduces the Zeta potential value of the coal particle surface by 63.73 mV. Therefore, the binary mixed collector can make the coal particles have good hydrophobicity and dispersibility, and can obviously improve the flotation effect of low-rank coal slime.The binary mixed collector prepared from diesel and oleic acid can be used as a new type of collector for the efficient development and utilization of low-rank coal slime.